Polyadenylated mRNA staining reveals distinct neuronal phenotypes following endothelin 1, focal brain ischemia, and global brain ischemia/ reperfusion - Jamison, Jill T. (2011)
OBJECTIVES: Most work on ischemia-induced neuronal death has revolved around the relative contributions of necrosis and apoptosis, but this work has not accounted for the role of ischemia-induced stress responses. An expanded view recognizes a competition between ischemia-induced damage mechanisms and stress responses in the genesis of ischemia-induced neuronal death. An important marker of post-ischemic stress responses is inhibition of neuronal protein synthesis, a morphological correlate of which is the compartmentalization of mRNA away from ribosomes in the form of cytoplasmic mRNA granules. METHODS: Here we assessed the generality of this mRNA granule response following either 10 or 15 minutes global brain ischemia and 1 hour reperfusion, 4 hours focal cerebral ischemia alone, and endothelin 1 intraventricular injection. RESULTS: Both global and focal ischemia led to prominent neuronal cytoplasmic mRNA granule formation in layer II cortical neurons. In addition, we report here new post-ischemic cellular phenotypes characterized by the loss of nuclear polyadenylated mRNA staining in cortical neurons following endothelin 1 treatment and 15 minutes global ischemia. Both mRNA granulation and loss of nuclear mRNAs occurred in non-shrunken post-ischemic neurons. DISCUSSION: Where cytoplasmic mRNA granules generally appear to mark a protective response in surviving cells, loss of nuclear mRNAs may mark cellular damage leading to cell atrophy/death. Hence, staining for total mRNA may reveal facets of the competition between stress responses and damage mechanisms at early stages in post-ischemic neurons.